Methods and applications for advancing distance education technologies : international issues and solutions - Syed, Mahbubur Rahman, 1952- (Hershey, PA : Information Science Reference, 2009)
'This book is for academic researchers and engineers who work with distance learning programs and software systems, as well as general users of distance education technologies and methods including computational methods, algorithms, implemented prototype systems, and applications of open and distance learning'--Provided by publisher.
Includes bibliographical references (p. 364-390) and index.
Keywords: Distance education -- Technological innovations; Educational technology